Conductive copper-based slurry for laminated solid aluminum capacitor core and preparation method and application of conductive copper-based slurry

By adjusting the composition and preparation process of the conductive copper-based slurry, the problems of high cost of conductive silver paste and high curing temperature of conductive copper paste are solved, low-temperature curing and high performance stability are achieved, production costs are reduced and capacitor reliability is improved.

CN119786267APending Publication Date: 2025-04-08XIAMEN TONGLE TECH CO LTD

Patent Information

Application Number
CN202510037602.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The conductive silver paste for existing solid aluminum capacitors is costly, and the conductive copper paste has a high curing temperature, high energy consumption, high viscosity and poor leveling after surface immersion, resulting in poor ESR stability.

Method used

By adjusting the composition and preparation process of the conductive copper-based slurry, low temperature curing, low energy consumption, low viscosity and good leveling are achieved, ensuring the uniformity of the film thickness after the capacitor core is impregnated.

Benefits of technology

It reduces production costs, optimizes the physical and chemical properties of the slurry, and improves the performance stability and reliability of the capacitor.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119786267A_ABST
    Figure CN119786267A_ABST
Patent Text Reader

Abstract

The invention provides conductive copper-based slurry for a laminated solid aluminum capacitor core and a preparation method and application of the conductive copper-based slurry, and relates to the technical field of solid aluminum capacitors. The conductive copper-based slurry for the laminated solid aluminum capacitor core comprises the following components in parts by weight: 40-60 parts of conductive filler, 5-15 parts of polymer resin and 30-50 parts of solvent, the conductive filler is antioxidant copper powder and / or silver coated copper powder. The conductive copper-based slurry is a high-solid-content and low-viscosity system, the dip-coating process is adapted by regulating and controlling the ratio of the conductive filler to the organic carrier, and high conductivity under low-temperature air curing is achieved; by reasonably adding the anti-settling agent, the dispersing agent, the solvent and other organic carriers, it is ensured that the slurry meets the requirements for viscosity and suspension property of the dipping process, slurry settling is effectively prevented, the film thickness uniformity after dipping, pulling and curing and the equivalent series resistance stability of a finally obtained capacitor core are ensured, and the performance stability and reliability of a capacitor are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of capacitor conductive materials, and in particular to a conductive copper-based slurry for a laminated solid aluminum capacitor core, and a preparation method and application thereof. Background Art

[0002] Capacitors are one of the three basic passive electronic components (resistors, capacitors and inductors), and they play an important role in the electronic component industry, with a global market size of over 10 billion US dollars. Capacitors mainly play the role of tuning, filtering, coupling, bypassing and energy conversion in circuits. In the field of traditional capacitors, they can be divided into four categories according to the different insulating media: aluminum electrolytic capacitors, tantalum electrolytic capacitors, ceramic capacitors and film capacitors. In recent years, with the high frequency of switching power supply circuits of electronic equipment, electrolytic capacitors with excellent high frequency characteristics are needed. As a new type of aluminum electrolytic capacitor, the laminated solid aluminum capacitor uses a conductive polymer material with high conductivity as a solid electrolyte, and has the advantages of high unit volume capacity, low ESR (equivalent series resistance), long life, high reliability, small size, and matching SMT process.

[0003] Solid aluminum electrolytic capacitors are formed by forming an oxide as a dielectric layer on an aluminum substrate, and making an electrolyte cathode layer and a cathode lead layer on the dielectric layer to form a capacitor, and the cathode lead layer is composed of a carbon layer and a silver layer. In the existing lamination process technology, carbon paste and silver paste are used to impregnate the capacitor core, and the single core is superimposed by bonding with conductive silver glue. The parameters of carbon paste, silver paste and silver glue will directly affect the resistance of the carbon layer and the silver layer, thereby affecting the ESR value of the capacitor.

[0004] Currently, the main conductive silver paste is on the market, but due to the high price of silver and the existence of problems such as silver ion migration in capacitor components, the service life of the capacitor is greatly affected, so other metal fillers are urgently needed to replace it. The volume resistivity of copper metal is similar to that of silver, but its price is only 1 / 21 of the price of silver, making it an ideal substitute for silver filler in the preparation of conductive paste. The conductive copper paste used on ceramic capacitors is widely used in high-temperature atmosphere sintering, but high-temperature sintered copper paste is not suitable for solid aluminum electrolytic capacitors. It is crucial to use low-temperature curing conductive copper paste in the conductive material of solid aluminum electrolytic capacitors. Capacitive membrane switches are mainly screen printing processes, and there is relatively little research on conductive copper paste used in impregnation processes. Research on replacing silver-based conductive pastes with low-cost, highly conductive copper-based pastes is urgently needed.

[0005] CN101354961A discloses a method for preparing a conductive copper paste for ceramic capacitors. The copper paste is composed of solvents such as pine alcohol, ethyl cellulose, phenolic resin, borosilicate glass powder, ultrafine copper powder, etc., and is bright red. It belongs to a sintered copper paste under high temperature atmosphere protection. The ceramic capacitor is made by screen printing on a ceramic substrate and sintering at high temperature in a nitrogen protection furnace. Its electrical properties such as capacity and loss can meet the technical requirements of ceramic capacitors. CN1545111A discloses a conductive paste for chip capacitor terminal electrodes, with silver or copper powder, zinc borosilicate glass powder, organic binder (methacrylic resin or acrylic resin) and solvent as main components. The paste significantly improves the accumulation state of solid particles, and the conductor after sintering has good compactness, greatly reduces the micropores on the surface of the conductor, and has good resistance to electroplating solution erosion. However, high-temperature sintering conductive copper paste requires high-temperature curing and protective atmosphere, and consumes a lot of energy.

[0006] CN109979686A discloses a low-temperature conductive copper paste and its preparation method. It uses silver-coated copper powder, which is relatively expensive, and the powder particle size used is 5-15μm. The curing temperature cannot reach below 200°C. The curing temperature is still relatively high, which is harmful to other materials in the core. CN112940564A discloses a low-temperature sintered copper paste, its preparation method and application. It is sintered at a low temperature of 180-300°C and passes through a printing process, but can only be used for 5G base station antennas with substrates that are not resistant to high temperatures; CN114005575A discloses an antioxidant conductive copper paste and its preparation method and application. Although the paste can be cured at a low temperature below 200°C, the screen printing process has a viscosity of 180-350Pa.s and is polished. The viscosity of the conductive copper paste in these two patents is large and is not suitable for the immersion process.

[0007] In view of this, the present invention is proposed. Summary of the invention

[0008] The purpose of the present invention is to provide a conductive copper-based slurry for a laminated solid aluminum capacitor core and a preparation method and application thereof. The conductive copper-based slurry is intended to solve the problem of high cost of conductive silver paste for existing solid aluminum capacitors, while overcoming the defects of the existing conductive copper slurry, such as high curing temperature, high energy consumption, high viscosity, and poor leveling after surface impregnation, which leads to large difference in film thickness between the upper and lower ends, thereby affecting ESR stability. Through the innovative design of the present invention, the conductive copper-based slurry not only reduces the production cost, but also optimizes the physical and chemical properties of the slurry, making it more suitable for the manufacture of laminated solid aluminum capacitors. Specifically, the present invention achieves low-temperature curing, low energy consumption, low viscosity and good leveling by adjusting the composition and preparation process of the slurry, thereby ensuring the uniformity of the film thickness of the capacitor core after impregnation, and improving the performance stability and reliability of the capacitor.

[0009] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0010] In a first aspect, the present invention provides a conductive copper-based slurry for a laminated solid aluminum capacitor core, wherein the conductive copper-based slurry for a laminated solid aluminum capacitor core comprises, by weight:

[0011] Conductive filler 40-60 parts

[0012] 5-15 parts polymer resin

[0013] 30-50 parts of solvent;

[0014] Wherein, the conductive filler is anti-oxidation copper powder and / or silver-coated copper powder.

[0015] Preferably, the antioxidant copper powder includes any one of spherical antioxidant copper powder, quasi-spherical antioxidant copper powder, flaky antioxidant copper powder or dendritic antioxidant copper powder, or a combination of at least two of them.

[0016] Preferably, the average particle size of each group of the spherical antioxidant copper powder or quasi-spherical antioxidant copper powder is independently 0.05 to 1.0 μm.

[0017] Preferably, the average particle size of the flaky anti-oxidation copper powder is 1 to 10 μm.

[0018] Preferably, the average particle size of the dendritic antioxidant copper powder is 3 to 15 μm.

[0019] Preferably, the silver-coated copper powder includes any one of spherical silver-coated copper powder, quasi-spherical silver-coated copper powder, flaky silver-coated copper powder or dendritic silver-coated copper powder, or a combination of at least two thereof.

[0020] Preferably, the average particle size of the spherical silver-coated copper powder or quasi-spherical silver-coated copper powder is 0.05-1.0 μm.

[0021] Preferably, the average particle size of the flaky silver-coated copper powder is 1 to 10 μm.

[0022] Preferably, the average particle size of the dendritic silver-coated copper powder is 3 to 15 μm.

[0023] Preferably, the conductive filler is a combination of any two of spherical antioxidant copper powder, quasi-spherical antioxidant copper powder, flaky antioxidant copper powder, dendritic antioxidant copper powder, spherical silver-coated copper powder, quasi-spherical silver-coated copper powder, flaky silver-coated copper powder or dendritic silver-coated copper powder.

[0024] Preferably, the conductive filler is a combination of spherical silver-coated copper powder and flaky antioxidant copper powder in a mass ratio of 1:(3-5), or a combination of quasi-spherical antioxidant copper powder and flaky antioxidant copper powder in a mass ratio of 1:(3-5).

[0025] Preferably, the conductive filler is a combination of spherical silver-coated copper powder and flaky silver-coated copper powder in a mass ratio of 1:(3-5), or a combination of quasi-spherical antioxidant copper powder and flaky silver-coated copper powder in a mass ratio of 1:(3-5).

[0026] Preferably, the conductive filler is a combination of dendritic silver-coated copper powder and flaky silver-coated copper powder in a mass ratio of 1:(8-10).

[0027] Preferably, the conductive filler is a combination of flaky anti-oxidation copper powder and flaky silver-coated copper powder in a mass ratio of 1:(3-5).

[0028] Preferably, the antioxidant copper powder is copper powder modified by a formate-containing compound and an organic thiol.

[0029] Preferably, the copper powder includes any one of spherical copper powder, quasi-spherical copper powder, flake copper powder or dendritic copper powder, or a combination of at least two thereof.

[0030] Preferably, the antioxidant copper powder is prepared by the following steps:

[0031] (a) dispersing copper powder in a polar solvent, adding an aqueous solution containing a reducing acid, and stirring to obtain a mixed solution;

[0032] (b) adding an aqueous solution containing a formate compound to the mixed solution to react, standing and stratifying after the reaction is completed, and removing the supernatant to obtain a formate-modified copper powder;

[0033] (c) adding an organic mercaptan to the formate-modified copper powder to carry out a reaction, standing the reaction to separate the layers, removing the supernatant, and washing, filtering, and drying to obtain the antioxidant copper powder.

[0034] Preferably, in step (a), the polar solvent comprises ethylene glycol.

[0035] Preferably, in step (a), the reducing acid comprises antioxidant acid.

[0036] Preferably, in step (a), the concentration of the aqueous solution containing reducing acid is 0.05 to 2 g / mL.

[0037] Preferably, in step (a), the dispersion is ultrasonic dispersion, and the dispersion time is 5 to 15 minutes.

[0038] Preferably, in step (a), the stirring treatment time is 20 to 40 minutes.

[0039] Preferably, in step (b), the formate compound comprises any one of formic acid, sodium formate, potassium formate or ammonium formate, or a combination of at least two thereof.

[0040] Preferably, in step (b), the concentration of the aqueous solution containing the formate compound is 0.5 to 3 g / mL.

[0041] Preferably, in step (b), the reaction temperature is 120-140° C., and the reaction time is 1-3 h.

[0042] Preferably, in step (c), the organic mercaptan includes any one or a combination of at least two of dodecyl mercaptan, tetradecyl mercaptan, hexadecyl mercaptan, ethanedithiol, 1-propanethiol or 1,3-propanedithiol.

[0043] Preferably, in step (c), the reaction temperature is 5 to 50° C., and the reaction time is 1 to 3 hours.

[0044] Preferably, the mass ratio of the copper powder, the reducing acidic compound, the formate-containing compound and the organic thiol is 1:(0.015-0.065):(0.050-0.450):(0.0005-0.0025).

[0045] Preferably, the polymer resin includes any one or a combination of at least two of bisphenol A epoxy resin, o-methylphenol epoxy resin, polyester resin, polyvinyl butyral, polyurethane resin, modified acrylate resin, amino resin, ethyl cellulose, chloroacetate resin, carboxyl-terminated nitrile rubber, polybutadiene rubber, thermosetting phenolic resin, and polyester polyol, preferably any one or a combination of at least two of polyvinyl butyral resin, modified acrylate resin, o-methylphenol epoxy resin, bisphenol A epoxy resin, polyurethane resin, or thermosetting phenolic resin.

[0046] Preferably, the solvent includes any one or a combination of at least two of diethylene glycol butyl ether acetate, propylene glycol methyl ether acetate, DBE, cyclohexanone, isopropanol, n-butanol, 1-octanol, butyl acetate, and ethyl acetate, preferably any one or a combination of at least two of diethylene glycol butyl ether acetate, DBE or n-butanol.

[0047] Preferably, the conductive copper-based slurry for the laminated solid aluminum capacitor core further includes 0.1 to 3 parts of a curing agent.

[0048] Preferably, the curing agent includes any one or a combination of at least two of modified imidazole, blocked isocyanate, thermosetting phenolic resin, maleic anhydride, methyltetrahydrophthalic anhydride or blocked phosphate cationic thermal initiator, preferably maleic anhydride.

[0049] Preferably, the conductive copper-based slurry for the laminated solid aluminum capacitor core further comprises 0.2 to 2 parts of an auxiliary agent.

[0050] Preferably, the auxiliary agent includes any one of a leveling agent, an anti-settling agent, a dispersant or a promoter, or a combination of at least two of them.

[0051] Preferably, the leveling agent includes any one of the acrylic leveling agent BYK-358N, the fluorocarbon modified acrylic leveling agent or the silicone leveling agent 333, or a combination of at least two thereof.

[0052] Preferably, the anti-settling agent includes any one of polyamide wax, BYK-410 or fumed silica, or a combination of at least two of them.

[0053] Preferably, the dispersant includes 7423, Any one of 221P or AFB-1521, or a combination of at least two of them.

[0054] Preferably, the accelerator includes any one of DMP-30, 2-ethyl-4-methylimidazole, triethanolamine, benzyldimethylamine or a quaternary ammonium salt, or a combination of at least two thereof.

[0055] In a second aspect, the present invention provides a method for preparing the conductive copper-based slurry for the laminated solid aluminum capacitor core as described in the first aspect, the preparation method comprising:

[0056] (1) mixing and stirring a polymer resin and a solvent to obtain a slurry 1;

[0057] (2) adding a conductive filler to the slurry 1 and stirring to obtain slurry 2;

[0058] (3) dispersing the slurry 2 and then grinding it to obtain slurry 3;

[0059] (4) Filtering the slurry three to obtain the conductive copper-based slurry for the laminated solid aluminum capacitor core.

[0060] Preferably, in step (1), the rotation speed of the mixing and stirring is 200 to 1000 rpm, and the time of the mixing and stirring is 20 to 60 min.

[0061] Preferably, step (1) also includes adding and mixing auxiliary agents.

[0062] Preferably, in step (2), the stirring speed is 200 to 800 rpm, and the stirring time is 30 to 60 min.

[0063] Preferably, step (2) also includes adding and mixing a curing agent.

[0064] Preferably, in step (3), the dispersing is carried out in a planetary mixer.

[0065] Preferably, in step (3), the dispersion speed is 20 to 80 rpm, and the dispersion time is 30 to 90 min.

[0066] Preferably, in step (3), the grinding is carried out in a three-roll mill.

[0067] Preferably, in step (3), the grinding parameters include: the feed roller spacing is set to 10-80 μm, the grinding times are 3-9 times, the speed ratio of the three rollers is (1-3): (2-6): (4-10), and the speed of the low roller is 60-260 rpm.

[0068] Preferably, in step (3), the fineness of the slurry three is less than 10 μm.

[0069] Preferably, in step (4), the mesh size of the filtration is 200 to 600 meshes.

[0070] In a third aspect, the present invention provides a use of the conductive copper-based slurry for a laminated solid aluminum capacitor core as described in the first aspect in preparing a conductive copper-based core of a solid aluminum capacitor.

[0071] In a fourth aspect, the present invention provides a solid aluminum capacitor conductive copper-based core, the solid aluminum capacitor conductive copper-based core comprising a solid aluminum capacitor core body and a conductive copper layer;

[0072] Wherein, the conductive copper layer is a conductive copper layer formed by sintering the conductive copper-based slurry for the laminated solid aluminum capacitor core as described in the first aspect.

[0073] In a fifth aspect, the present invention provides a method for preparing the conductive copper-based core of the solid aluminum capacitor according to the fourth aspect, the preparation method comprising:

[0074] The conductive copper-based slurry of the laminated solid aluminum capacitor core described in the first aspect is applied to the surface of the solid aluminum capacitor core body by dipping and pulling, and then dried and sintered to obtain the conductive copper-based core of the solid aluminum capacitor.

[0075] Preferably, the speed of the immersion pulling is 1 to 10 mm / min.

[0076] Preferably, the drying is carried out in an air-drying manner, the drying temperature is 10 to 40° C., and the drying time is 2 to 8 hours.

[0077] Preferably, the sintering temperature is 145-155° C., and the sintering time is 30-60 min.

[0078] Preferably, the thickness of the conductive copper layer is 20-50 μm.

[0079] In a sixth aspect, the present invention provides a solid aluminum capacitor, comprising the conductive copper-based core of the solid aluminum capacitor as described in the fourth aspect.

[0080] Compared with the prior art, the present invention has the following beneficial effects:

[0081] (1) Low-temperature curing: The conductive copper-based slurry for the laminated solid aluminum capacitor core of the present invention is a low-temperature conductive copper-based slurry. The slurry can be cured in air at about 150°C. Compared with the high-temperature curing conditions required for traditional conductive copper slurries, the present invention significantly reduces the curing temperature, thereby reducing energy consumption and production costs, and can achieve the purpose of energy saving and cost reduction. This feature makes the slurry more economical and practical in industrial production.

[0082] (2) Excellent anti-settling performance and maintaining slurry stability: By carefully selecting organic carrier components such as anti-settling agents, dispersants, and solvents, the present invention solves the sedimentation problem that is easily caused by the high density of metal powder under low viscosity. This innovative design effectively avoids the stratification of the organic phase and the metal phase in the slurry, ensuring that the slurry can remain in a uniform dispersion state during long-term standing or transportation. At the same time, the slurry can meet the strict requirements of the impregnation process on viscosity and suspension, and achieves the slurry is not easy to settle during use, ensuring the stability of the process and the consistency of product quality.

[0083] (3) Uniform film thickness and stable equivalent series resistance: The conductive copper-based slurry used in the laminated solid aluminum capacitor core of the present invention can maintain an excellent film thickness difference after impregnation, pulling and curing. This means that during the manufacturing process of the capacitor core, a uniform film thickness can be obtained at both the upper and lower ends. This feature is crucial to improving the performance of laminated solid aluminum capacitors because it can ensure that the ESR of the capacitor is more stable. A stable ESR has an important impact on the service life, energy efficiency and reliability of the capacitor, thereby improving the overall performance and market competitiveness of the capacitor.

[0084] In view of the continuous exploration and pursuit of high-performance conductive materials in the current technical field, the present invention stands out for its novelty. Specifically, the present invention innovatively meets the urgent demand for high-performance slurries in the capacitor manufacturing field by improving the preparation process and formula of conductive copper-based slurries, showing remarkable novelty. This includes precise control of key parameters (such as temperature and time) in the preparation process, as well as the optimization of dispersants and stabilizers, in order to obtain a new conductive copper-based slurry with significantly improved conductivity, dispersibility and stability, thereby achieving a novel breakthrough in material formulation.

[0085] In terms of creativity, the present invention is committed to solving the problems of performance fluctuation and uneven dispersion encountered by traditional conductive pastes in capacitor applications. Through innovative solutions, the present invention not only fundamentally improves the overall performance and reliability of capacitors, but also demonstrates a high degree of creativity. In addition, considering the actual needs of industrial production, the preparation method proposed in the present invention has been deeply explored in terms of efficiency and scalability, providing a practical path for large-scale and continuous production of conductive copper-based pastes, further demonstrating its creativity in preparation strategies.

[0086] In terms of practicality, the conductive copper-based paste designed by the patent of this invention is specially optimized for the needs of laminated solid aluminum capacitor cores, realizing practical applications in the field of laminated solid aluminum capacitors, but its application range goes far beyond this. With its excellent conductivity, dispersibility and stability, the paste shows a wide range of applicability in the manufacture of various types of capacitors and electronic components, reflecting its practical value. More importantly, the paste may also have environmental advantages such as low-temperature curing and low energy consumption, which helps to reduce production costs and improve production efficiency, thereby occupying a favorable position in market competition, further highlighting its practicality in laminated capacitors and other practical applications.

[0087] In summary, the patent of this invention has demonstrated outstanding novelty, creativity and practicality in the material formula, preparation strategy and broad application prospects of the conductive copper-based slurry. It aims to solve the key problems currently faced in the capacitor manufacturing field and promote the continuous development of related technologies. BRIEF DESCRIPTION OF THE DRAWINGS

[0088] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0089] Figure 1 The present invention is a process flow chart of a method for preparing a conductive copper-based slurry for a laminated solid aluminum capacitor core.

[0090] Figure 2 The present invention is a process flow chart of the method for preparing the conductive copper-based core of the solid aluminum capacitor.

[0091] Figure 3 This is a SEM image of the conductive layer formed by the conductive copper-based paste of the laminated solid aluminum capacitor core provided in Example 1 before the double 85 test.

[0092] Figure 4This is a SEM image of the conductive layer formed by the conductive copper-based paste of the laminated solid aluminum capacitor core provided in Example 1 after 1000 hours of double 85 test. DETAILED DESCRIPTION

[0093] Unless otherwise defined herein, scientific and technical terms used in conjunction with the present invention shall have the meanings commonly understood by those of ordinary skill in the art. The meaning and scope of the terms should be clear, however, in the case of any potential ambiguity, the definitions provided herein take precedence over any dictionary or external definitions. In this application, unless otherwise stated, the use of "or" means "and / or". In addition, the use of the term "including" and other forms is non-limiting.

[0094] It should be noted that specific details are described in the following description to facilitate a full understanding of the present invention. However, the present invention can be implemented in a variety of other ways different from those described herein, and those skilled in the art can make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0095] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0096] In a first aspect, the present invention provides a conductive copper-based slurry for a laminated solid aluminum capacitor core, wherein the conductive copper-based slurry for a laminated solid aluminum capacitor core comprises, by weight:

[0097] Conductive filler 40-60 parts

[0098] 5-15 parts polymer resin

[0099] 30-50 parts of solvent;

[0100] Wherein, the conductive filler is anti-oxidation copper powder and / or silver-coated copper powder.

[0101] In the present invention, the conductive copper-based slurry for the laminated solid aluminum capacitor core is regulated by other organic carriers such as anti-settling agents, dispersants, solvents, etc., which solves the problem of easy sedimentation due to the high density of metal powder under low viscosity, and well avoids the phenomenon of stratification between the organic phase and the metal phase of the slurry, which can meet the viscosity and suspension required by the impregnation process, and realize that the slurry is not easy to settle. Among them, the conductive filler is antioxidant copper powder and / or silver-coated copper powder, which can play a good conductive role, and the powders contact each other to form a conductive path; in addition, the present invention can further limit the shape and size of the powder, enhance the contact between the powders, and increase the purpose of conductivity. Among them, the polymer resin acts as a bonding powder, acts with a curing agent, and connects the resin molecules, so that the conductive powder is evenly distributed in the resin matrix. Among them, the solvent can dissolve or dilute the resin and other organic substances in the slurry, adjust the viscosity and fluidity of the slurry, and affect the drying speed and production efficiency during the slurry coating process.

[0102] As an optional embodiment of the present invention, in the conductive copper-based slurry, the content of the conductive filler is 40 to 60 parts, for example, it can be 40 parts, 42 parts, 44 parts, 46 parts, 48 ​​parts, 50 parts, 52 parts, 54 parts, 56 parts, 58 parts, 60 parts, etc.

[0103] As an optional embodiment of the present invention, in the conductive copper-based paste, the content of the polymer resin is 5 to 15 parts, for example, it can be 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, etc.

[0104] As an optional embodiment of the present invention, in the conductive copper-based slurry, the content of the solvent is 30 to 50 parts, for example, it can be 30 parts, 32 parts, 34 parts, 36 parts, 38 parts, 40 parts, 42 parts, 44 parts, 46 parts, 48 ​​parts, 50 parts, etc.

[0105] As an optional embodiment of the present invention, the antioxidant copper powder includes any one of spherical antioxidant copper powder, quasi-spherical antioxidant copper powder, flaky antioxidant copper powder or dendritic antioxidant copper powder, or a combination of at least two of them.

[0106] As an optional embodiment of the present invention, the average particle size of each group of the spherical antioxidant copper powder or quasi-spherical antioxidant copper powder is independently 0.05 to 1.0 μm, for example, it can be 0.05 μm, 0.06 μm, 0.08 μm, 0.1 μm, 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1.0 μm, etc.

[0107] As an optional embodiment of the present invention, the average particle size of the flaky antioxidant copper powder is 1 to 10 μm, for example, it can be 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, etc.

[0108] As an optional embodiment of the present invention, the average particle size of the dendritic antioxidant copper powder is 3 to 15 μm, for example, it can be 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, etc.

[0109] As an optional embodiment of the present invention, the silver-coated copper powder includes any one of spherical silver-coated copper powder, quasi-spherical silver-coated copper powder, flaky silver-coated copper powder or dendritic silver-coated copper powder, or a combination of at least two thereof.

[0110] As an optional embodiment of the present invention, the average particle size of the spherical silver-coated copper powder or quasi-spherical silver-coated copper powder is 0.05 to 1.0 μm, for example, it can be 0.05 μm, 0.06 μm, 0.08 μm, 0.1 μm, 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1.0 μm, etc.

[0111] As an optional embodiment of the present invention, the average particle size of the flaky silver-coated copper powder is 1 to 10 μm, for example, it can be 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, etc.

[0112] As an optional embodiment of the present invention, the average particle size of the dendritic silver-coated copper powder is 3 to 15 μm, for example, it can be 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, etc.

[0113] As an optional embodiment of the present invention, the conductive filler is a combination of any two of spherical antioxidant copper powder, quasi-spherical antioxidant copper powder, flaky antioxidant copper powder, dendritic antioxidant copper powder, spherical silver-coated copper powder, quasi-spherical silver-coated copper powder, flaky silver-coated copper powder or dendritic silver-coated copper powder.

[0114] As an optional embodiment of the present invention, the conductive filler is a combination of spherical silver-coated copper powder and flaky antioxidant copper powder in a mass ratio of 1:(3-5), or a combination of quasi-spherical antioxidant copper powder and flaky antioxidant copper powder in a mass ratio of 1:(3-5), preferably a combination of spherical silver-coated copper powder and flaky antioxidant copper powder in a mass ratio of 1:4, or a combination of quasi-spherical antioxidant copper powder and flaky antioxidant copper powder in a mass ratio of 1:4.

[0115] As an optional embodiment of the present invention, the conductive filler is a combination of spherical silver-coated copper powder and flaky silver-coated copper powder in a mass ratio of 1:(3-5), or a combination of quasi-spherical antioxidant copper powder and flaky silver-coated copper powder in a mass ratio of 1:(3-5), preferably a combination of spherical silver-coated copper powder and flaky silver-coated copper powder in a mass ratio of 1:4, or a combination of quasi-spherical antioxidant copper powder and flaky silver-coated copper powder in a mass ratio of 1:4.

[0116] As an optional embodiment of the present invention, the conductive filler is a combination of dendritic silver-coated copper powder and flaky silver-coated copper powder in a mass ratio of 1:(8-10), preferably a combination of dendritic silver-coated copper powder and flaky silver-coated copper powder in a mass ratio of 1:9.

[0117] As an optional embodiment of the present invention, the conductive filler is a combination of flaky antioxidant copper powder and flaky silver-coated copper powder in a mass ratio of 1:(3-5), preferably a combination of flaky antioxidant copper powder and flaky silver-coated copper powder in a mass ratio of 1:4.

[0118] As an optional embodiment of the present invention, the antioxidant copper powder is copper powder modified by a formate-containing compound and an organic thiol.

[0119] As an optional embodiment of the present invention, the copper powder includes any one of spherical copper powder, quasi-spherical copper powder, flake copper powder or dendritic copper powder, or a combination of at least two thereof.

[0120] As an optional embodiment of the present invention, the antioxidant copper powder is prepared by the following steps:

[0121] (a) dispersing copper powder in a polar solvent, adding an aqueous solution containing a reducing acid, and stirring to obtain a mixed solution;

[0122] (b) adding an aqueous solution containing a formate compound to the mixed solution to react, standing and stratifying after the reaction is completed, and removing the supernatant to obtain a formate-modified copper powder;

[0123] (c) adding an organic mercaptan to the formate-modified copper powder to carry out a reaction, standing the reaction to separate the layers, removing the supernatant, and washing, filtering, and drying to obtain the antioxidant copper powder.

[0124] As an optional embodiment of the present invention, in step (a), the copper powder includes any one of spherical copper powder, quasi-spherical copper powder, flake copper powder or dendritic copper powder, or a combination of at least two thereof.

[0125] As an optional embodiment of the present invention, in step (a), the polar solvent includes ethylene glycol.

[0126] As an optional embodiment of the present invention, in step (a), the reducing acid includes antioxidant acid.

[0127] As an optional embodiment of the present invention, in step (a), the concentration of the aqueous solution containing reducing acid is 0.05-2 g / mL, for example, it can be 0.05 g / mL, 0.06 g / mL, 0.08 g / mL, 0.1 g / mL, 0.2 g / mL, 0.4 g / mL, 0.6 g / mL, 0.8 g / mL, 1 g / mL, 1.2 g / mL, 1.4 g / mL, 1.6 g / mL, 1.8 g / mL, 2 g / mL, etc.

[0128] As an optional embodiment of the present invention, in step (a), the dispersion is ultrasonic dispersion, and the dispersion time is 5 to 15 minutes, for example, it can be 5 minutes, 6 minutes, 7 minutes, 8 minutes, 9 minutes, 10 minutes, 11 minutes, 12 minutes, 13 minutes, 14 minutes, 15 minutes, etc.

[0129] As an optional embodiment of the present invention, in step (a), the stirring treatment time is 20 to 40 min, for example, it can be 20 min, 22 min, 24 min, 26 min, 28 min, 30 min, 32 min, 34 min, 36 min, 38 min, 40 min, etc.

[0130] As an optional embodiment of the present invention, in step (b), the formate compound includes any one of formic acid, sodium formate, potassium formate or ammonium formate, or a combination of at least two thereof.

[0131] As an optional embodiment of the present invention, in step (b), the concentration of the aqueous solution containing the formate compound is 0.5-3 g / mL, for example, it can be 0.5 g / mL, 0.6 g / mL, 0.8 g / mL, 1 g / mL, 1.2 g / mL, 1.5 g / mL, 2 g / mL, 2.5 g / mL, 3 g / mL, etc.

[0132] As an optional embodiment of the present invention, in step (b), the reaction temperature is 120-140°C, for example, 120°C, 125°C, 130°C, 135°C, 140°C, etc., and the reaction time is 1-3h, for example, 1h, 1.5h, 2h, 2.5h, 3h, etc.

[0133] As an optional embodiment of the present invention, in step (c), the organic mercaptan includes any one of dodecyl mercaptan, tetradecyl mercaptan, hexadecyl mercaptan, ethanedithiol, 1-propanethiol or 1,3-propanedithiol, or a combination of at least two thereof.

[0134] As an optional embodiment of the present invention, in step (c), the reaction temperature is 5 to 50°C, for example, it can be 5°C, 10°C, 15°C, 20°C, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, etc., and the reaction time is 1 to 3h, for example, it can be 1h, 1.5h, 2h, 2.5h, 3h, etc.

[0135] As an optional embodiment of the present invention, the mass ratio of copper powder, reducing acidic, formate-containing compound and organic thiol is 1:(0.015-0.065):(0.050-0.450):(0.0005-0.0025);

[0136] Here, “0.015-0.065” may be, for example, 0.015, 0.020, 0.025, 0.030, 0.035, 0.040, 0.045, 0.050, 0.055, 0.060, 0.065, etc.;

[0137] Here, “0.050-0.450” may be, for example, 0.050, 0.100, 0.150, 0.200, 0.250, 0.300, 0.350, 0.400, 0.450, etc.;

[0138] Here, “0.0005 to 0.0025” may be, for example, 0.0005, 0.0010, 0.0015, 0.0020, 0.0025, etc.

[0139] As an optional embodiment of the present invention, the polymer resin includes any one or a combination of at least two of bisphenol A epoxy resin, o-methylphenol epoxy resin, polyester resin, polyvinyl butyral, polyurethane resin, modified acrylate resin, amino resin, ethyl cellulose, chloroacetate resin, carboxyl-terminated nitrile rubber, polybutadiene rubber, thermosetting phenolic resin, and polyester polyol, preferably any one or a combination of at least two of polyvinyl butyral resin, modified acrylate resin, o-methylphenol epoxy resin, bisphenol A epoxy resin, polyurethane resin, or thermosetting phenolic resin.

[0140] As an optional embodiment of the present invention, the solvent includes any one of diethylene glycol butyl acetate, propylene glycol methyl ether acetate, DBE, cyclohexanone, isopropanol, n-butanol, 1-octanol, butyl acetate, and ethyl acetate, or a combination of at least two of them, preferably any one of diethylene glycol butyl acetate, DBE or n-butanol, or a combination of at least two of them, preferably a combination of diethylene glycol butyl acetate, DBE and n-butanol.

[0141] As an optional embodiment of the present invention, in the conductive copper-based slurry, the content of the curing agent is 0.1 to 3 parts, for example, it can be 0.1 part, 0.2 part, 0.4 part, 0.6 part, 0.8 part, 1 part, 1.2 parts, 1.4 parts, 1.6 parts, 1.8 parts, 2 parts, 2.2 parts, 2.4 parts, 2.6 parts, 2.8 parts, 3 parts, etc.

[0142] As an optional embodiment of the present invention, the curing agent includes any one or a combination of at least two of modified imidazole, blocked isocyanate, thermosetting phenolic resin, maleic anhydride, methyltetrahydrophthalic anhydride or blocked phosphate cationic thermal initiator, preferably maleic anhydride.

[0143] As an optional embodiment of the present invention, in the conductive copper-based paste, the content of the auxiliary agent is 0.2 to 2 parts, for example, 0.2 parts, 0.4 parts, 0.6 parts, 0.8 parts, 1 parts, 1.2 parts, 1.4 parts, 1.6 parts, 1.8 parts, 2 parts, etc.

[0144] As an optional embodiment of the present invention, the auxiliary agent includes any one of a leveling agent, an anti-settling agent, a dispersant or a promoter, or a combination of at least two of them.

[0145] In the present invention, the dispersant is used to reduce the surface tension of the slurry, so that the solid-liquid two phases in the slurry form a uniform and stable mixture. The anti-settling agent mainly slows down the sedimentation of the powder in the slurry, while improving the thixotropy and viscosity of the slurry and improving the rheological properties of the slurry. The leveling agent can promote the slurry to form a flat, smooth and uniform coating during the drying and film-forming process. The accelerator mainly improves the adhesion between the carbon slurry layer substrate and the coating, and enhances the chemical reaction and curing process of the slurry.

[0146] As an optional embodiment of the present invention, the leveling agent includes any one of the acrylic leveling agent BYK-358N, the fluorocarbon modified acrylic leveling agent or the silicone leveling agent 333, or a combination of at least two thereof.

[0147] As an optional embodiment of the present invention, the anti-settling agent includes any one of polyamide wax, BYK-410 or fumed silica, or a combination of at least two of them.

[0148] As an optional embodiment of the present invention, the dispersant includes 7423, Any one of 221P or AFB-1521, or a combination of at least two of them.

[0149] As an optional embodiment of the present invention, the accelerator includes any one of DMP-30, 2-ethyl-4-methylimidazole, triethanolamine, benzyldimethylamine or a quaternary ammonium salt, or a combination of at least two thereof.

[0150] In a second aspect, the present invention provides a method for preparing a conductive copper-based slurry for a laminated solid aluminum capacitor core as described in the first aspect, such as Figure 1 As shown, the preparation method comprises:

[0151] (1) mixing and stirring a polymer resin and a solvent to obtain a slurry 1;

[0152] (2) adding a conductive filler to the slurry 1 and stirring to obtain slurry 2;

[0153] (3) dispersing the slurry 2 and then grinding it to obtain slurry 3;

[0154] (4) Filtering the slurry three to obtain the conductive copper-based slurry for the laminated solid aluminum capacitor core.

[0155] As an optional embodiment of the present invention, in step (1), the rotation speed of the mixing and stirring is 200 to 1000 rpm, for example, it can be 200 rpm, 300 rpm, 400 rpm, 500 rpm, 600 rpm, 700 rpm, 800 rpm, 900 rpm, 1000 rpm, etc., and the mixing and stirring time is 20 to 60 min, for example, it can be 20 min, 30 min, 40 min, 50 min, 60 min, etc.

[0156] As an optional embodiment of the present invention, step (1) further includes adding and mixing auxiliary agents.

[0157] As an optional embodiment of the present invention, when the conductive copper-based slurry contains an additive, step (1) is: mixing and stirring the polymer resin, the additive and the solvent to obtain slurry one.

[0158] As an optional embodiment of the present invention, in step (2), the stirring speed is 200-800 rpm, for example, it can be 200 rpm, 250 rpm, 300 rpm, 350 rpm, 400 rpm, 450 rpm, 500 rpm, 550 rpm, 600 rpm, 650 rpm, 700 rpm, 750 rpm, 800 rpm, etc., and the stirring time is 30-60 min, for example, it can be 30 min, 35 min, 40 min, 45 min, 50 min, 55 min, 60 min, etc.

[0159] As an optional embodiment of the present invention, step (2) further includes adding and mixing a curing agent.

[0160] As an optional embodiment of the present invention, in step (2), when the conductive copper-based slurry contains a curing agent, step (2) is: adding a conductive filler and a curing agent to the slurry one, and stirring to obtain a slurry two.

[0161] As an optional embodiment of the present invention, in step (3), the dispersing is carried out in a planetary mixer.

[0162] As an optional embodiment of the present invention, in step (3), the dispersion rotation speed is 20 to 80 rpm, for example, it can be 20 rpm, 30 rpm, 40 rpm, 50 rpm, 60 rpm, 70 rpm, 80 rpm, etc., and the dispersion time is 30 to 90 min, for example, it can be 30 min, 35 min, 40 min, 45 min, 50 min, 55 min, 60 min, 65 min, 70 min, 75 min, 80 min, 85 min, 90 min, etc.

[0163] As an optional embodiment of the present invention, in step (3), the grinding is carried out in a three-roll grinder.

[0164] As an optional embodiment of the present invention, in step (3), the grinding parameters include: the feed roller spacing is set to 10 to 80 μm, for example, it can be 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, etc., the grinding number is 3 to 9 times, for example, it can be 3 times, 4 times, 5 times, 6 times, 7 times, 8 times, 9 times, etc., and the speed ratio of the three rollers is (1 to 3): (2 to 6): (4 to 10), for example, it can be 1:2: 4, 1:3:5, 1:4:6, 1:5:8, 1:6:10, 2:3:4, 2:4:5, 2:5:6, 2:5:7, 3:2:4, 3:3:5, 3:4:6, 3:4:7, 3:6:10, etc. The rotation speed of the low roller is 60 to 260 rpm, for example, it can be 60 rpm, 70 rpm, 80 rpm, 100 rpm, 120 rpm, 150 rpm, 200 rpm, 250 rpm, 260 rpm, etc.

[0165] As an optional embodiment of the present invention, in step (3), the fineness of the slurry three is less than 10 μm, for example, it can be 10 μm, 9 μm, 8 μm, 7 μm, 6 μm, 5 μm, 4 μm, 3 μm, 2 μm, 1 μm, etc.

[0166] As an optional embodiment of the present invention, in step (4), the mesh size of the filtration is 200-600 mesh, for example, it can be 200 mesh, 250 mesh, 300 mesh, 350 mesh, 400 mesh, 450 mesh, 500 mesh, 550 mesh, 600 mesh, etc.

[0167] In a third aspect, the present invention provides a use of the conductive copper-based slurry for a laminated solid aluminum capacitor core as described in the first aspect in preparing a conductive copper-based core of a solid aluminum capacitor.

[0168] In a fourth aspect, the present invention provides a solid aluminum capacitor conductive copper-based core, the solid aluminum capacitor conductive copper-based core comprising a solid aluminum capacitor core body and a conductive copper layer;

[0169] Wherein, the conductive copper layer is a conductive copper layer formed by sintering the conductive copper-based slurry for the laminated solid aluminum capacitor core as described in the first aspect.

[0170] In a fifth aspect, the present invention provides a method for preparing the conductive copper-based core of the solid aluminum capacitor according to the fourth aspect, such as Figure 2 As shown, the preparation method comprises:

[0171] The conductive copper-based slurry of the laminated solid aluminum capacitor core described in the first aspect is applied to the surface of the solid aluminum capacitor core body by dipping and pulling, and then dried and sintered to obtain the conductive copper-based core of the solid aluminum capacitor.

[0172] As an optional embodiment of the present invention, the immersion pulling speed is 1 to 10 mm / min, for example, it can be 1 mm / min, 2 mm / min, 3 mm / min, 4 mm / min, 5 mm / min, 6 mm / min, 7 mm / min, 8 mm / min, 9 mm / min, 10 mm / min, etc.

[0173] As an optional embodiment of the present invention, the drying is carried out in an air-drying manner, the drying temperature is 10-40°C, for example, 10°C, 15°C, 20°C, 25°C, 30°C, 35°C, 40°C, etc., and the drying time is 2-8h, for example, 2h, 3h, 4h, 5h, 6h, 7h, 8h, etc.

[0174] As an optional embodiment of the present invention, the sintering temperature is 145-155°C, for example, it can be 140°C, 146°C, 148°C, 150°C, 152°C, 154°C, 155°C, etc., and the sintering time is 30-60 min.

[0175] As an optional embodiment of the present invention, the thickness of the conductive copper layer is 20-50 μm, for example, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, etc.

[0176] In a sixth aspect, the present invention provides a solid aluminum capacitor, comprising the conductive copper-based core of the solid aluminum capacitor as described in the fourth aspect.

[0177] The present invention is further described below by way of examples. Unless otherwise specified, the materials in the examples are prepared according to existing methods or directly purchased from the market.

[0178] The sources of the components in the following examples are as follows:

[0179]

[0180] Preparation Example 1

[0181] This preparation example provides a flaky antioxidant copper powder, which is prepared by the following steps:

[0182] (a) After ultrasonically dispersing flaky copper powder with a particle size of 1 to 10 μm in ethylene glycol for 10 minutes, a 1 g / mL aqueous solution of sodium hypochlorite was added and stirred for 30 minutes to obtain a mixed solution;

[0183] (b) adding a 2 g / mL aqueous solution of sodium formate to the mixed solution, reacting at 130° C. for 2 h, standing and stratifying after the reaction, and removing the supernatant to obtain formate-modified copper powder;

[0184] (c) adding 40 mL of tetradecyl mercaptan to the formate-modified copper powder, reacting at 25° C. for 2 h, standing the reaction to separate layers, removing the supernatant, washing, filtering, and drying to obtain flaky antioxidant copper powder with a particle size of 1 to 10 μm.

[0185] Preparation Example 2

[0186] This preparation example provides a spherical antioxidant copper powder, which is prepared by the following steps:

[0187] (a) after ultrasonically dispersing spherical copper powder with a particle size of 0.05 to 1.0 μm in ethylene glycol for 10 minutes, adding a 0.5 g / mL aqueous solution of sodium hypochlorite, stirring for 30 minutes, and obtaining a mixed solution;

[0188] (b) adding a 2 g / mL aqueous solution of ammonium formate to the mixed solution, reacting at 130° C. for 2 h, standing and stratifying after the reaction, and removing the supernatant to obtain formate-modified copper powder;

[0189] (c) adding 40 mL of hexadecyl mercaptan to the formate-modified copper powder, reacting at 25° C. for 2 h, standing the reaction to separate layers, removing the supernatant, washing, filtering, and drying to obtain spherical antioxidant copper powder with a particle size of 0.05 to 1.0 μm.

[0190] Preparation Example 3

[0191] This preparation example provides a modified acrylate resin, which is prepared by the following steps:

[0192] 50 g of hydroxyethyl methacrylate and 50 g of BR113 acrylic resin are placed in a four-necked flask containing 400 g of butyl acetate, mixed and stirred to dissolve into a transparent liquid; an initiator, dimethyl azobisisobutyrate, is added and stirred until dissolved, and the amount of initiator used is 1 g; the four-necked flask is placed in an ultrasonic constant temperature pool, and nitrogen is slowly introduced for 30 minutes to remove the oxygen in the bottle; after the temperature is raised to 70°C, the ultrasonic power is set to 300 W, and the ultrasound is turned on to carry out an ultrasonic polymerization reaction; the ultrasonic time is controlled to 5 hours, and the reaction is closed after 5 hours to obtain a viscous modified acrylic resin solution.

[0193] Example 1

[0194] This embodiment provides a conductive copper-based slurry for a laminated solid aluminum capacitor core, and the conductive copper-based slurry for a laminated solid aluminum capacitor core includes the following components in parts by weight:

[0195] Conductive filler: 50 parts of 1-10μm flake silver-coated copper powder

[0196]

[0197] The conductive copper-based slurry for the laminated solid aluminum capacitor core is prepared by the following steps:

[0198] S1, take 5 parts of polyester resin, and add 2 parts of polyvinyl butyral resin, 10 parts of DBE solvent, 10 parts of diethylene glycol butyl ether acetate, 22 parts of n-butanol, 0.5 parts of silicone leveling agent 333, 0.5 parts of anti-settling agent polyamide wax in sequence, mix and stir at a speed of 300 rpm for 30 minutes to obtain slurry 1;

[0199] S2, adding 50 parts of 1-10 μm flaky silver-coated copper powder into slurry 1 at a stirring speed of 600 rpm, and fully mixing and stirring at a speed of 800 rpm for 30 minutes to obtain slurry 2;

[0200] S3, transferring the slurry 2 to a planetary mixer, stirring and dispersing at a speed of 40 rpm for 60 min; then passing the slurry 2 through a three-roll mill for dispersion grinding, with the feed roller spacing set to 10 μm, the grinding times being 3 times, the speed ratio of the three rollers being 1:2:4, the speed of the low roller being 100 rpm, and obtaining a slurry 3 with a fineness of less than 10 μm;

[0201] S4. Finally, the slurry is filtered through a 400-mesh screen to obtain the conductive copper-based slurry for the laminated solid aluminum capacitor core.

[0202] Example 2

[0203] This embodiment provides a conductive copper-based slurry for a laminated solid aluminum capacitor core, and the conductive copper-based slurry for a laminated solid aluminum capacitor core includes the following components in parts by weight:

[0204]

[0205]

[0206] The conductive copper-based slurry for the laminated solid aluminum capacitor core is prepared by the following steps:

[0207] S1, take 5 parts of modified acrylic resin, and add 1 part of o-methylphenolic epoxy resin, 10 parts of DBE solvent, 10 parts of diethylene glycol butyl ether acetate, 22 parts of n-butanol, 1 part of triethanolamine, 0.7 parts of acrylic leveling agent BYK-358N, 0.5 parts of anti-settling agent polyamide wax, mix and stir at a speed of 300 rpm for 25 minutes to obtain slurry 1;

[0208] S2, adding 0.8 parts of blocked isocyanate curing agent, 10 parts of 1-10 μm flaky copper powder, and 40 parts of 1-10 μm flaky silver-coated copper powder to slurry one at a stirring speed of 600 rpm, and fully mixing and stirring at a speed of 800 rpm for 30 minutes to obtain slurry two;

[0209] S3, transferring the slurry 2 to a planetary mixer, stirring and dispersing at a speed of 40 rpm for 60 min; then passing the slurry 2 through a three-roll mill for dispersion grinding, with the feed roller spacing set to 10 μm, the grinding times being 3 times, the speed ratio of the three rollers being 1:2:4, the speed of the low roller being 100 rpm, and obtaining a slurry 3 with a fineness of less than 10 μm;

[0210] S4. Finally, the slurry is filtered through a 400-mesh screen to obtain the conductive copper-based slurry for the laminated solid aluminum capacitor core.

[0211] Example 3

[0212] This embodiment provides a conductive copper-based slurry for a laminated solid aluminum capacitor core, and the conductive copper-based slurry for a laminated solid aluminum capacitor core includes the following components in parts by weight:

[0213]

[0214]

[0215] The conductive copper-based slurry for the laminated solid aluminum capacitor core is prepared by the following steps:

[0216] S1, take 5 parts of modified acrylic resin, and add 1 part of o-methylphenolic epoxy resin, 20 parts of DBE solvent, 10 parts of diethylene glycol butyl ether acetate, 11.8 parts of n-butanol, 1 part of triethanolamine, 0.7 parts of acrylic leveling agent BYK-358N, 0.5 parts of anti-settling agent polyamide wax and 1 part of amino resin in sequence, mix and stir at a speed of 300 rpm for 30 minutes to obtain slurry 1;

[0217] S2, adding 10 parts of 1-10 μm flaky antioxidant copper powder and 40 parts of 1-10 μm flaky silver-coated copper powder into slurry 1 at a stirring speed of 600 rpm, and fully mixing and stirring at a speed of 800 rpm for 30 minutes to obtain slurry 2;

[0218] S3, transferring the slurry 2 to a planetary mixer, stirring and dispersing at a speed of 40 rpm for 60 min; then passing the slurry 2 through a three-roll mill for dispersion grinding, with the feed roller spacing set to 10 μm, the grinding times being 3 times, the speed ratio of the three rollers being 1:2:4, the speed of the low roller being 100 rpm, and obtaining a slurry 3 with a fineness of less than 10 μm;

[0219] S4. Finally, the slurry is filtered through a 400-mesh screen to obtain the conductive copper-based slurry for the laminated solid aluminum capacitor core.

[0220] Example 4

[0221] This embodiment provides a conductive copper-based slurry for a laminated solid aluminum capacitor core, and the conductive copper-based slurry for a laminated solid aluminum capacitor core includes the following components in parts by weight:

[0222]

[0223] The conductive copper-based slurry for the laminated solid aluminum capacitor core is prepared by the following steps:

[0224] S1, take 5 parts of bisphenol A epoxy resin, and add 10 parts of DBE solvent, 10 parts of diethylene glycol butyl ether acetate, 21 parts of n-butanol, 3 parts of thermosetting phenolic resin, 0.5 parts of silicone leveling agent 333, 0.5 parts of anti-settling agent polyamide wax, mix and stir at a speed of 300 rpm for 30 minutes to obtain slurry 1;

[0225] S2, adding 5 parts of 3-15 μm dendritic silver-coated copper powder and 45 parts of 1-10 μm flake silver-coated copper powder into slurry 1 at a stirring speed of 600 rpm, and fully mixing and stirring at a speed of 800 rpm for 30 minutes to obtain slurry 2;

[0226] S3, transferring the slurry 2 to a planetary mixer, stirring and dispersing at a speed of 40 rpm for 60 min; then passing the slurry 2 through a three-roll mill for dispersion grinding, with the feed roller spacing set to 10 μm, the grinding times being 3 times, the speed ratio of the three rollers being 1:2:4, the speed of the low roller being 100 rpm, and obtaining a slurry 3 with a fineness of less than 10 μm;

[0227] S4. Finally, the slurry is filtered through a 400-mesh screen to obtain the conductive copper-based slurry for the laminated solid aluminum capacitor core.

[0228] Example 5

[0229] This embodiment provides a conductive copper-based slurry for a laminated solid aluminum capacitor core, and the conductive copper-based slurry for a laminated solid aluminum capacitor core includes the following components in parts by weight:

[0230]

[0231] The conductive copper-based slurry for the laminated solid aluminum capacitor core is prepared by the following steps:

[0232] S1, take 5 parts of bisphenol A epoxy resin, and add 10 parts of DBE solvent, 10 parts of diethylene glycol butyl ether acetate, 22 parts of n-butanol, 0.5 parts of silicone leveling agent 333, 0.5 parts of anti-settling agent polyamide wax, 1 part of 2-ethyl-4-methylimidazole in sequence, mix and stir at a speed of 300 rpm for 30 minutes to obtain slurry 1;

[0233] S2, adding 1 part of maleic anhydride, 5 parts of 3-15 μm dendritic silver-coated copper powder and 45 parts of 1-10 μm flake silver-coated copper powder into slurry 1 at a stirring speed of 600 rpm, and fully mixing and stirring at a speed of 800 rpm for 30 minutes to obtain slurry 2;

[0234] S3, transferring the slurry 2 to a planetary mixer, stirring and dispersing at a speed of 40 rpm for 60 min; then passing the slurry 2 through a three-roll mill for dispersion grinding, with the feed roller spacing set to 10 μm, the grinding times being 3 times, the speed ratio of the three rollers being 1:2:4, the speed of the low roller being 100 rpm, and obtaining a slurry 3 with a fineness of less than 10 μm;

[0235] S4. Finally, the slurry is filtered through a 400-mesh screen to obtain the conductive copper-based slurry for the laminated solid aluminum capacitor core.

[0236] Example 6

[0237] This embodiment provides a conductive copper-based slurry for a laminated solid aluminum capacitor core, and the conductive copper-based slurry for a laminated solid aluminum capacitor core includes the following components in parts by weight:

[0238]

[0239] The conductive copper-based slurry for the laminated solid aluminum capacitor core is prepared by the following steps:

[0240] S1, take 10 parts of polyurethane resin, and add 20 parts of DBE solvent, 6 parts of diethylene glycol butyl ether acetate, 10 parts of cyclohexanone, 0.5 parts of silicone leveling agent 333, 0.5 parts of anti-settling agent polyamide wax, 3 parts of triethanolamine in sequence, mix and stir at a speed of 300 rpm for 30 minutes to obtain slurry 1;

[0241] S2, adding 10 parts of 0.05-1.0 μm spherical antioxidant copper powder and 40 parts of 1-10 μm flaky silver-coated copper powder into slurry 1 at a stirring speed of 600 rpm, and fully mixing and stirring at a speed of 800 rpm for 30 minutes to obtain slurry 2;

[0242] S3, transferring the slurry 2 to a planetary mixer, stirring and dispersing at a speed of 40 rpm for 60 min; then passing the slurry 2 through a three-roll mill for dispersion grinding, with the feed roller spacing set to 10 μm, the grinding times being 3 times, the speed ratio of the three rollers being 1:2:4, the speed of the low roller being 100 rpm, and obtaining a slurry 3 with a fineness of less than 10 μm;

[0243] S4. Finally, the slurry is filtered through a 400-mesh screen to obtain the conductive copper-based slurry for the laminated solid aluminum capacitor core.

[0244] Example 7

[0245] This embodiment provides a conductive copper-based slurry for a laminated solid aluminum capacitor core. The only difference from Example 1 is that the polyester resin content is increased to 10 parts and the n-butanol content is reduced to 17 parts. The other components and preparation steps are exactly the same as those in Example 1.

[0246] Example 8

[0247] This embodiment provides a conductive copper-based slurry for a laminated solid aluminum capacitor core. The only difference from Example 1 is that polyvinyl butyral resin is no longer added, the content of n-butanol is increased to 24 parts, and the other components and preparation steps are exactly the same as those in Example 1.

[0248] Example 9

[0249] This embodiment provides a conductive copper-based slurry for a laminated solid aluminum capacitor core. The only difference from Example 1 is that 0.5 parts of a thermosetting phenolic resin curing agent is added, the content of n-butanol is reduced to 21.5 parts, and the other components and preparation steps are exactly the same as those in Example 1.

[0250] Example 10

[0251] This embodiment provides a conductive copper-based slurry for a laminated solid aluminum capacitor core, which is different from Example 1 only in that the content of flaky silver-coated copper powder is increased to 60 parts, the content of DBE solvent is reduced to 7.6 parts, the content of diethylene glycol butyl ether acetate is reduced to 7.6 parts, and the content of n-butanol is reduced to 16.8 parts. The other components and preparation steps are exactly the same as those in Example 1.

[0252] Embodiment 11

[0253] This embodiment provides a conductive copper-based slurry for a laminated solid aluminum capacitor core, which is different from Example 1 only in that the conductive filler includes: 10 parts of 1-10 μm flaky antioxidant copper powder provided in Preparation Example 1, and 40 parts of 1-10 μm flaky silver-coated copper powder, and other components and preparation steps are exactly the same as Example 1.

[0254] Example 12

[0255] This embodiment provides a conductive copper-based slurry for a laminated solid aluminum capacitor core, which is different from Example 1 only in that the conductive filler includes: 10 parts of 0.05-1.0 μm spherical antioxidant copper powder provided in Preparation Example 2, and 40 parts of 1-10 μm flaky antioxidant copper powder provided in Preparation Example 1, and other components and preparation steps are exactly the same as in Example 1.

[0256] Embodiment 13

[0257] This embodiment provides a conductive copper-based slurry for a laminated solid aluminum capacitor core. The difference from Example 1 is that 0.5 parts of dispersant 7423 is added, the content of n-butanol is reduced to 21.5 parts, and other components and preparation steps are exactly the same as those in Example 1.

[0258] Embodiment 14

[0259] This embodiment provides a conductive copper-based slurry for a laminated solid aluminum capacitor core, which is different from the embodiment 1 only in that 0.5 parts of a dispersant is added. 221P, the n-butanol content is reduced to 21.5 parts, and the other components and preparation steps are exactly the same as those in Example 1.

[0260] Embodiment 15

[0261] This embodiment provides a conductive copper-based slurry for a laminated solid aluminum capacitor core, which is different from Example 1 only in that 0.5 parts of dispersant AFB-1521 is added, the content of n-butanol is reduced to 21.5 parts, and other components and preparation steps are exactly the same as those in Example 1.

[0262] Example 16

[0263] This embodiment provides a conductive copper-based slurry for a laminated solid aluminum capacitor core, and the conductive copper-based slurry for a laminated solid aluminum capacitor core includes the following components in parts by weight:

[0264]

[0265] The conductive copper-based slurry for the laminated solid aluminum capacitor core is prepared by the following steps:

[0266] S1, take 5 parts of polyester resin, and add 2 parts of polyvinyl butyral resin, 10 parts of DBE solvent, 10 parts of diethylene glycol butyl ether acetate, 21.5 parts of n-butanol, 0.5 parts of silicone leveling agent 333, 0.5 parts of anti-settling agent polyamide wax, 0.5 parts of dispersant 221P, fully mixed and stirred at a speed of 300 rpm for 30 min to obtain slurry 1;

[0267] S2, adding 10 parts of 0.05-1.0 μm spherical antioxidant copper powder provided in Preparation Example 2 and 40 parts of 1-10 μm flaky antioxidant copper powder provided in Preparation Example 1 to slurry 1 at a stirring speed of 600 rpm, and fully mixing and stirring at a speed of 800 rpm for 30 minutes to obtain slurry 2;

[0268] S3, transferring the slurry 2 to a planetary mixer, stirring and dispersing at a speed of 40 rpm for 60 min; then passing the slurry 2 through a three-roll mill for dispersion grinding, with the feed roller spacing set to 10 μm, the grinding times being 3 times, the speed ratio of the three rollers being 1:2:4, the speed of the low roller being 100 rpm, and obtaining a slurry 3 with a fineness of less than 10 μm;

[0269] S4. Finally, the slurry is filtered through a 400-mesh screen to obtain the conductive copper-based slurry for the laminated solid aluminum capacitor core.

[0270] Comparative Example 1

[0271] This comparative example provides a conductive copper-based slurry, which is different from Example 1 only in that the content of flaky silver-coated copper powder is reduced to 35 parts, the content of polyester resin is increased to 10 parts, the content of polyvinyl butyral resin is increased to 7 parts, and the content of n-butanol is increased to 27 parts. The other components and preparation steps are exactly the same as those in Example 1.

[0272] Comparative Example 2

[0273] This comparative example provides a conductive copper-based slurry, which is different from Example 1 only in that the content of flaky silver-coated copper powder is increased to 65 parts, the content of polyester resin is reduced to 2 parts, the content of polyvinyl butyral resin is reduced to 2 parts, and the content of n-butanol is reduced to 10 parts. The other components and preparation steps are exactly the same as those in Example 1.

[0274] Comparative Example 3

[0275] This comparative example provides a conductive copper-based slurry, which is different from Example 1 only in that the content of flaky silver-coated copper powder is increased to 70 parts, the content of polyester resin is increased to 10 parts, the content of polyvinyl butyral resin is increased to 4 parts, the content of DBE solvent is reduced to 5 parts, the content of diethylene glycol butyl ether acetate is reduced to 5 parts, and the content of n-butanol is reduced to 5 parts. The other components and preparation steps are exactly the same as those in Example 1.

[0276] Comparative Example 4

[0277] This comparative example provides a conductive copper-based slurry, which differs from Example 1 only in that the 1-10 μm flaky silver-coated copper powder is replaced with an equal mass of 1-10 μm ordinary flaky copper powder (without antioxidant treatment), and the other components and preparation steps are exactly the same as those in Example 1.

[0278] Comparative Example 5

[0279] This comparative example provides a conductive copper-based slurry, which is different from Example 1 only in that the silicone leveling agent 333 is not added, the content of polyamide wax 6900-20X is increased to 1 part, and the other components and preparation steps are completely consistent with Example 1.

[0280] Comparative Example 6

[0281] This comparative example provides a conductive copper-based slurry, which is different from Example 1 only in that polyamide wax 6900-20X is not added, the content of silicone leveling agent 333 is increased to 1 part, and other components and preparation steps are completely consistent with Example 1.

[0282] Comparative Example 7

[0283] This comparative example provides a conductive copper-based slurry, which is different from Example 1 only in that DBE solvent is no longer added to the solvent, the content of diethylene glycol butyl ether acetate is increased to 15 parts, and the content of n-butanol is increased to 27 parts. The other components and preparation steps are exactly the same as those in Example 1.

[0284] Comparative Example 8

[0285] This comparative example provides a conductive copper-based slurry, which is different from Example 1 only in that diethylene glycol butyl ether acetate is no longer added to the solvent, the DBE solvent content is increased to 15 parts, the n-butanol content is increased to 27 parts, and the other components and preparation steps are exactly the same as Example 1.

[0286] Comparative Example 9

[0287] This comparative example provides a conductive copper-based slurry, which is different from Example 1 only in that n-butanol is no longer added to the solvent, the DBE solvent content is increased to 21 parts, the diethylene glycol butyl ether acetate content is increased to 21 parts, and the other components and preparation steps are exactly the same as Example 1.

[0288] Test Case

[0289] Test samples: the conductive copper-based slurry for laminated solid aluminum capacitor core provided in Examples 1 to 16, and the conductive copper-based slurry provided in Comparative Examples 1 to 9.

[0290] Test method:

[0291] Each slurry sample was double-sidedly coated on a solid aluminum capacitor core (using an aluminum foil sheet with a conductive polymer and conductive carbon paste impregnated on the surface) or a PET film material using an immersion pulling process at a rate of 10 mm / min, hung to dry at room temperature, and then placed in an oven at a preset temperature (150°C) for low-temperature sintering for 60 minutes to obtain a single-piece solid aluminum capacitor conductive copper-based core or a conductive copper-based PET film material, and performance testing experiments were carried out on the obtained products.

[0292] The method of the conductive performance test experiment is: after collecting the block resistance with a four-pin block resistance tester, it is converted into a block resistance with a thickness of 25.4μm according to the thickness of the cured copper film and the block resistance, and the cured block resistance (unit: mΩ / sq) is tested under the condition of baking at 150°C for 60 minutes.

[0293] The test method and standard for adhesion is GB / T9826-1998.

[0294] Viscosity test standard: GB / T 2794, detect the equivalent series resistance ESR of the chip polymer laminated aluminum capacitor (use a precision LCR digital bridge to test the impedance of the capacitor monolithic chip), and record the sedimentation rate of the slurry (the slurry is placed in a centrifuge tube, and the time and height of the sedimentation and stratification of copper powder and organic liquid are regularly observed, mm / h).

[0295] The double 85 aging resistance test is to place the coating film in a hot and humid environment at 85°C and 85% relative humidity for 1000 hours after curing at 150°C for 60 minutes in Example 1 to test the change in its square resistance. The hot and humid test reflects the degree of oxidation resistance of the copper paste layer.

[0296] The test results are shown in Table 1 below:

[0297] Table 1

[0298]

[0299]

[0300] As shown in Table 1, the conductive copper-based slurry of the present invention is impregnated on the surface of the carbon slurry layer of the solid aluminum capacitor substrate, and cured in air at 150°C to obtain a single core that meets the technical requirements of the solid aluminum capacitor, reducing material costs and replacing the corresponding conductive silver slurry. The conductive layer formed by the conductive copper-based slurry of the laminated solid aluminum capacitor core provided in Example 1 is subjected to a double 85 aging test, and the square resistance value only changes from 12mΩ / sq to 12.6mΩ / sq.

[0301] And if Figure 3-4 As shown, the conductive layer formed by the conductive copper-based slurry for the laminated solid aluminum capacitor core provided in Example 1 has no significant difference in the SEM image after the double 85 test for 1000h, and the square resistance has almost no change, which proves that it has good oxidation resistance. The conductive slurry of the present invention is added with micro-nano-grade antioxidant copper powder and / or silver-coated copper powder, so that the prepared conductive copper-based slurry can be cured at a low temperature of 150°C in air, and is suitable for the preparation of solid aluminum capacitor elements. The slurry prepared by the present invention can meet the viscosity and suspension required by the impregnation process through the regulation of other organic carriers such as anti-settling agents, dispersants, solvents, etc., so that the slurry is not easy to settle, and maintains an excellent film thickness difference after impregnation and pulling curing.

[0302] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A conductive copper-based slurry for laminated solid aluminum capacitor core, characterized in that: The conductive copper-based slurry for the laminated solid aluminum capacitor core comprises, by weight: Conductive filler 40-60 parts 5-15 parts of polymer resin 30-50 parts of solvent; Wherein, the conductive filler is anti-oxidation copper powder and / or silver-coated copper powder.

2. The conductive copper-based slurry for laminated solid aluminum capacitor core according to claim 1, characterized in that: The antioxidant copper powder includes any one of spherical antioxidant copper powder, quasi-spherical antioxidant copper powder, flaky antioxidant copper powder or dendritic antioxidant copper powder, or a combination of at least two thereof; Preferably, the average particle size of each group of the spherical antioxidant copper powder or quasi-spherical antioxidant copper powder is independently 0.05 to 1.0 μm; Preferably, the average particle size of the flaky anti-oxidation copper powder is 1 to 10 μm; Preferably, the average particle size of the dendritic antioxidant copper powder is 3 to 15 μm; Preferably, the silver-coated copper powder includes any one of spherical silver-coated copper powder, quasi-spherical silver-coated copper powder, flaky silver-coated copper powder or dendritic silver-coated copper powder, or a combination of at least two thereof; Preferably, the average particle size of the spherical silver-coated copper powder or quasi-spherical silver-coated copper powder is 0.05 to 1.0 μm; Preferably, the average particle size of the flaky silver-coated copper powder is 1 to 10 μm; Preferably, the average particle size of the dendritic silver-coated copper powder is 3 to 15 μm; Preferably, the conductive filler is a combination of any two of spherical antioxidant copper powder, quasi-spherical antioxidant copper powder, flaky antioxidant copper powder, dendritic antioxidant copper powder, spherical silver-coated copper powder, quasi-spherical silver-coated copper powder, flaky silver-coated copper powder or dendritic silver-coated copper powder; Preferably, the conductive filler is a combination of spherical silver-coated copper powder and flaky antioxidant copper powder in a mass ratio of 1:(3-5), or a combination of quasi-spherical antioxidant copper powder and flaky antioxidant copper powder in a mass ratio of 1:(3-5); Preferably, the conductive filler is a combination of spherical silver-coated copper powder and flaky silver-coated copper powder in a mass ratio of 1:(3-5), or a combination of quasi-spherical antioxidant copper powder and flaky silver-coated copper powder in a mass ratio of 1:(3-5); Preferably, the conductive filler is a combination of dendritic silver-coated copper powder and flaky silver-coated copper powder in a mass ratio of 1:(8-10); Preferably, the conductive filler is a combination of flaky anti-oxidation copper powder and flaky silver-coated copper powder in a mass ratio of 1:(3-5); Preferably, the antioxidant copper powder is copper powder modified by a formate-containing compound and an organic thiol; Preferably, the copper powder includes any one of spherical copper powder, quasi-spherical copper powder, flake copper powder or dendritic copper powder, or a combination of at least two thereof.

3. The conductive copper-based slurry for laminated solid aluminum capacitor core according to claim 1 or 2, characterized in that: The antioxidant copper powder is prepared by the following steps: (a) dispersing copper powder in a polar solvent, adding an aqueous solution containing a reducing acid, and stirring to obtain a mixed solution; (b) adding an aqueous solution containing a formate compound to the mixed solution to react, standing and stratifying after the reaction is completed, and removing the supernatant to obtain a formate-modified copper powder; (c) adding an organic mercaptan to the formate-modified copper powder to carry out a reaction, standing the reaction to separate the layers, removing the supernatant, and washing, filtering, and drying to obtain the antioxidant copper powder; Preferably, in step (a), the polar solvent comprises ethylene glycol; Preferably, in step (a), the reducing acid comprises antioxidant acid; Preferably, in step (a), the concentration of the aqueous solution containing reducing acid is 0.05 to 2 g / mL; Preferably, in step (a), the dispersion is ultrasonic dispersion, and the dispersion time is 5 to 15 minutes; Preferably, in step (a), the stirring time is 20 to 40 minutes; Preferably, in step (b), the formate compound comprises any one or a combination of at least two of formic acid, sodium formate, potassium formate or ammonium formate; Preferably, in step (b), the concentration of the aqueous solution containing the formate compound is 0.5 to 3 g / mL; Preferably, in step (b), the reaction temperature is 120-140° C., and the reaction time is 1-3 h; Preferably, in step (c), the organic mercaptan includes any one or a combination of at least two of dodecyl mercaptan, tetradecyl mercaptan, hexadecyl mercaptan, ethanedithiol, 1-propanethiol or 1,3-propanedithiol; Preferably, in step (c), the reaction temperature is 5 to 50° C., and the reaction time is 1 to 3 hours; Preferably, the mass ratio of the copper powder, the reducing acidic compound, the formate-containing compound and the organic thiol is 1:(0.015-0.065):(0.050-0.450):(0.0005-0.0025).

4. The conductive copper-based slurry for laminated solid aluminum capacitor core according to claim 1, characterized in that: The polymer resin includes any one or a combination of at least two of bisphenol A epoxy resin, o-methylphenol epoxy resin, polyester resin, polyvinyl butyral, polyurethane resin, modified acrylate resin, amino resin, ethyl cellulose, chloroacetate resin, carboxyl-terminated nitrile rubber, polybutadiene rubber, thermosetting phenolic resin, and polyester polyol, preferably any one or a combination of at least two of polyvinyl butyral resin, modified acrylate resin, o-methylphenol epoxy resin, bisphenol A epoxy resin, polyurethane resin, or thermosetting phenolic resin; Preferably, the solvent includes any one or a combination of at least two of diethylene glycol butyl ether acetate, propylene glycol methyl ether acetate, DBE, cyclohexanone, isopropanol, n-butanol, 1-octanol, butyl acetate, and ethyl acetate, preferably any one or a combination of at least two of diethylene glycol butyl ether acetate, DBE or n-butanol; Preferably, the conductive copper-based slurry for the laminated solid aluminum capacitor core further includes 0.1 to 3 parts of a curing agent; Preferably, the curing agent comprises any one or a combination of at least two of modified imidazole, blocked isocyanate, thermosetting phenolic resin, maleic anhydride, methyltetrahydrophthalic anhydride or blocked phosphate cationic thermal initiator, preferably maleic anhydride; Preferably, the conductive copper-based slurry for the laminated solid aluminum capacitor core further includes 0.2 to 2 parts of an auxiliary agent; Preferably, the auxiliary agent includes any one or a combination of at least two of a leveling agent, an anti-settling agent, a dispersant or a promoter; Preferably, the leveling agent includes any one of the acrylic leveling agent BYK-358N, the fluorocarbon modified acrylic leveling agent or the silicone leveling agent 333, or a combination of at least two thereof; Preferably, the anti-settling agent comprises any one of polyamide wax, BYK-410 or fumed silica, or a combination of at least two thereof; Preferably, the dispersant includes 7423, Any one of 221P or AFB-1521 or a combination of at least two; Preferably, the accelerator includes any one of DMP-30, 2-ethyl-4-methylimidazole, triethanolamine, benzyldimethylamine or a quaternary ammonium salt, or a combination of at least two thereof.

5. A method for preparing a conductive copper-based slurry for a laminated solid aluminum capacitor core according to any one of claims 1 to 4, characterized in that: The preparation method comprises: (1) mixing and stirring a polymer resin and a solvent to obtain a slurry 1; (2) adding a conductive filler to the slurry 1 and stirring to obtain slurry 2; (3) dispersing the slurry 2 and then grinding it to obtain slurry 3; (4) Filtering the slurry three to obtain the conductive copper-based slurry for the laminated solid aluminum capacitor core.

6. The method for preparing the conductive copper-based slurry for laminated solid aluminum capacitor core according to claim 5, characterized in that: In step (1), the mixing speed is 200 to 1000 rpm, and the mixing time is 20 to 60 min; Preferably, step (1) further comprises adding and mixing an auxiliary agent; Preferably, in step (2), the stirring speed is 200 to 800 rpm, and the stirring time is 30 to 60 min; Preferably, step (2) further includes adding and mixing a curing agent; Preferably, in step (3), the dispersing is carried out in a planetary mixer; Preferably, in step (3), the dispersion speed is 20 to 80 rpm, and the dispersion time is 30 to 90 min; Preferably, in step (3), the grinding is carried out in a three-roll grinder; Preferably, in step (3), the grinding parameters include: the feed roller spacing is set to 10-80 μm, the grinding times are 3-9 times, the speed ratio of the three rollers is (1-3): (2-6): (4-10), and the speed of the low roller is 60-260 rpm; Preferably, in step (3), the fineness of the slurry three is less than 10 μm; Preferably, in step (4), the mesh size of the filtration is 200 to 600 meshes.

7. Use of the conductive copper-based slurry for a laminated solid aluminum capacitor core according to any one of claims 1 to 4 in preparing a conductive copper-based core of a solid aluminum capacitor.

8. A conductive copper-based core of a solid aluminum capacitor, characterized in that: The solid aluminum capacitor conductive copper-based core comprises a solid aluminum capacitor core body and a conductive copper layer; Wherein, the conductive copper layer is formed by sintering the conductive copper-based slurry for the laminated solid aluminum capacitor core according to any one of claims 1 to 4.

9. A method for preparing a conductive copper-based core of a solid aluminum capacitor according to claim 8, characterized in that: The preparation method comprises: The conductive copper-based slurry for the laminated solid aluminum capacitor core according to any one of claims 1 to 4 is applied to the surface of the solid aluminum capacitor core body by dipping and pulling, and then dried and sintered to obtain the conductive copper-based core of the solid aluminum capacitor; Preferably, the speed of the dipping and pulling is 1 to 10 mm / min; Preferably, the drying is carried out in an air-drying manner, the drying temperature is 10 to 40° C., and the drying time is 2 to 8 hours; Preferably, the sintering temperature is 145-155°C, and the sintering time is 30-60 minutes; Preferably, the thickness of the conductive copper layer is 20-50 μm.

10. A solid aluminum capacitor, characterized in that: The solid aluminum capacitor comprises the solid aluminum capacitor conductive copper-based core as claimed in claim 8.

Citation Information

Patent Citations

  • Method for preparing conductive cuprum slurry for ceramic capacitor electrode

    CN101354961A

  • Low-temperature conductive copper paste and preparation method thereof

    CN109979686A

  • Low-temperature sintered copper paste, preparation method and application

    CN112940564A

  • Anti-oxidation conductive copper slurry as well as preparation method and application thereof

    CN114005575A

  • Conductive pulp for terminal electrode of chip capacitor

    CN1545111A

Cited By

  • Preparation method and application of low-viscosity copper powder in slurry

    CN120839059A

  • A method for preparing low-viscosity copper powder in slurry and application thereof

    CN120839059B